Microspectrometer-Enabled Real-Time Concentration Monitoring in the Microfluidic Protein Enrichment Chip - Dong-Li Li; Wen-Shu Huang; Yi Hung Wu; Chun-Ping Jen (Biosensors)
This study presents a novel microspectrometer-integrated microfluidic system for real-time protein concentration monitoring. The device employs electrokinetic principles for efficient protein preconcentration in a PDMS and Nafion film channel. Using FITC-labeled BSA as a model protein, the system demonstrated a linear correlation between protein concentration and absorbance at 491 nm. Notably, it achieved a 833-fold concentration increase from an initial 10 nM within 20 min. The compact microspectrometer system offers enhanced accuracy and sensitivity compared to traditional fluorescence microscopy methods. This innovation presents a promising solution for portable and point-of-care diagnostic applications, facilitating timely disease detection and monitoring. The findings highlight the potential for this technology to advance protein analysis and biomarker discovery in clinical settings, potentially improving patient outcomes through enhanced diagnostic capabilities.